2023
DOI: 10.3389/fpsyg.2022.1087065
|View full text |Cite
|
Sign up to set email alerts
|

Perceived socially responsible-HRM on talent retention: The mediating effect of trust and motivation and the moderating effect of other-regarding value orientation

Abstract: IntroductionStudies have shown that there is a growing interest in corporate social responsibility (CSR) and talent management, and the identified links between their aspects. Thus, the current study examined the relationship between socially responsible human resource management (SRHRM)–identified as CSR strategies and practices directed at employees to underpin the effectiveness of CSR implementation–and talent retention. In addition, this study employed a mediation-moderation framework with employee attitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 114 publications
0
4
0
1
Order By: Relevance
“…Pentingnya tanggung jawab sosial bermula dari masyarakat sebagai regulasi kelembagaan dan organisasi bisnis untuk meningkatkan citra publik dan meningkatkan profitabilitas (Rawshdeh et al, 2023). Faktanya, CSR adalah salah satu alat penting bagi organisasi bisnis untuk mendapatkan keunggulan kompetitif.…”
Section: Pendahuluanunclassified
“…Pentingnya tanggung jawab sosial bermula dari masyarakat sebagai regulasi kelembagaan dan organisasi bisnis untuk meningkatkan citra publik dan meningkatkan profitabilitas (Rawshdeh et al, 2023). Faktanya, CSR adalah salah satu alat penting bagi organisasi bisnis untuk mendapatkan keunggulan kompetitif.…”
Section: Pendahuluanunclassified
“…According to assumptions made on the SET and SIT, having a high level of ISQ reduces employee turnover by increasing the cost of leaving the organization and increasing the dependence of employees and commitment, along with obligation to the organization and a feeling of connection and attachment to a specific organization (Briggs et al, 2020; Jiang et al, 2012; Mitchell et al, 2001; Shaw et al, 2009). In this regard, Rawshdeh et al (2023) found out that when companies invest in HRM and ISQ programs, more retention will be secured for their talented employees. Saleem et al (2022) in their analysis of employee performance, concluded that employee performance and productivity form a key tool for securing competitiveness.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…The second measurement is qualitative; it is more complex, for it goes beyond the limits of the formal parameters of HRM. Here we speak of labor conditions—friendliness of personnel, unity of work teams, attentiveness and individual approach of the management to each employee, and comfort of workplaces (Chtioui et al, 2023 ; Rawshdeh et al, 2023 ). These conditions, in their totality, determine the opportunities for unlocking of human potential of the employees and their receiving satisfaction from labor; that is why, they have an important place in Maslow’s pyramid of needs (Vu, 2022 ).…”
Section: Literature Reviewmentioning
confidence: 99%